Big Data - Definitions and Applicability, an Example of Unemployement Forecatsing - Kuźmiar, Sławomir (Studia Oeconomica Posnaniensia, 2019)
In the era of the growing informatization of the world the term Big Data seems to be one of the most recent and popular issues concerning economic and social analysis according both to functioning economic agents, economic policy or real business. Due to the growing amount and accessibility to Big Data, the main objective of this paper is an attempt to define the term Big Data and categorize its main sources. Additionally, this paper aims to present possibilities for implementing Big Data in economic studies, particularly an assessment of Google trends Data as a useful tool for nowcasting and forecasting economic indicators of the Polish labour market (i.e. unemployment) is presented. The obtained results indicated that the addition of an additional variable determining the number of specific Internet queries related to the job seeking process raised the forecasting properties of the model forecasting the level of unemployment in Poland.